Pre-diabetes is associated with altered functional connectivity density in cortical regions of the default-mode network - Lopez-Vilaret, Karel M.; Fernandez-Alvarez, Marina; Shokri-Kojori, Ehsan; Tomasi, Dardo; Cantero, Jose L.; Atienza, Mercedes (Frontiers in Aging Neuroscience, 2022)
Insulin resistance and glucose dysregulation are associated with patterns of regional brain hypometabolism characteristic of Alzheimer's disease (AD). As predicted by evidence linking brain glucose metabolism to brain functional connectivity, type 2 diabetes is accompanied by altered functional connectivity density (FCD) in regions highly vulnerable to AD, but whether these alterations start at earlier stages such as pre-diabetes remain to be elucidated. Here, in addition to assessing whether pre-diabetes leads to a functional reorganization of densely connected cortical areas (hubs), we will assess whether such reorganization is conditioned by sex and/or insulin resistance, and contributes to improved cognition. One hundred and forty-four cognitively unimpaired middle-aged and older adults (55-78 years, 79 females), 73 with normoglycemia and 71 with pre-diabetes, underwent resting-state fMRI scanning. We first computed FCD mapping on cortical surfaces to determine the number of short- and long-range functional connections of every vertex in the cortex, and next used hubs showing aberrant FCD as seeds for the resting-state functional connectivity (rs-FC) calculation. ANCOVAs and linear multiple regression analyses adjusted by demographic and cardiometabolic confounders using frequentist and Bayesian approaches were applied. Analyses revealed higher long-range FCD in the right precuneus of pre-diabetic females and lower short-range FCD in the left medial orbitofrontal cortex (mOFC) of pre-diabetic individuals with higher insulin resistance. Although the mOFC also showed altered rs-FC patterns with other regions of the default mode network in pre-diabetic individuals, it was FCD of the precuneus and mOFC, and not the magnitude of their rs-FC, that was associated with better planning abilities and Mini-Mental State Examination (MMSE) scores. Results suggest that being female and/or having high insulin resistance exacerbate pre-diabetes-induced alterations in the FCD of hubs of the default-mode network that are particularly vulnerable to AD pathology. These changes in brain network organization appear to be compensatory for pre-diabetic females, likely assisting them to maintain cognitive functioning at early stages of glucose dysregulation.